Dosimetric properties of dysprosium doped lithium borate glass irradiated by 6 MV photons. (July 2015) - Ab Rasid, A.; Wagiran, H.; Hashim, S.; Ibrahim, Z.; Ali, H.
Abstract: Undoped and dysprosium doped lithium borate glass system with empirical formula (70– x ) B2 O3 –30 Li2 O–( x ) Dy2 O3 ( x =0.1, 0.3, 0.5, 0.7, 1.0 mol%) were prepared using the melt-quenching technique. The dosimetric measurements were performed by irradiating the samples to 6 MV photon beam using linear accelerator (LINAC) over a dose range of 0.5–5.0 Gy. The glass series of dysprosium doped lithium borate glass produced the best thermoluminescence (TL) glow curve with the highest intensity peak from sample with 1.0 mol% Dy2 O3 concentration. Minimum detectable dose was detected at 2.24 mGy, good linearity of regression coefficient, high reproducibility and high sensitivity compared to the undoped glass are from 1.0 mol% dysprosium doped lithium borate glass. The results indicated that the series of dysprosium doped lithium glasses have a great potential to be considered as a thermoluminescence dosimetry (TLD). Highlights: TL response of undoped and dysprosium doped lithium borate glass subjected to 6 MV photons irradiation at low dose range. TL linear response of dysprosium doped lithium borate glass. The sensitivity of dysprosium doped lithium borate glass is approximately 93 times higher than undoped glass.